Error Analysis towards Scientific Paper’s Abstract Written by the Second Period of Graduation of Social Sciences and Political Students of University of Riau Kepulauan in 2019/2020 Academic Year - Jefriadi, (Proceeding of International Conference on Language Pedagogy (ICOLP), 2022)
Making mistakes is a natural activity in any learning process since mistakes are the flaws in learner speaking or writing. Writers cannot learn and perfect the language unless they make blunders on a regular basis. The study and assessment of linguistic doubt is known as error analysis. Error analysis may also be defined as an attempt to calculate and analyze the errors of the learners that could not be expanded or given by contrastive analysis. The analysis is based on library research to acquire data such textbooks, journals, articles, virtual resources, and internet access. The data analysis technique is descriptive technique procedures in which the researcher interprets and comprehends the text and content analysis. The scientific article' abstract produced by students from Second Period of Graduation of Social Sciences and Political students at University of Riau Kepulauan in 2019/2020 Academic Year is the primary reference for this research. In conducting the research, the writer analyzed 9 abstracts of students’ undergraduate theses in the Social and Political Science Faculty. Based on the analysis, the writer found errors in abstracts that were categorized into four kinds of errors. namely addition errors, omission errors, misformation errors, and misordering errors. There are 11 different types of errors found in the process of analyzing the data with 2 addition error, 5 omission error, 2 misordering error and 2 misformation error.